Incidence of Spontaneous Obliteration in Untreated Brain Arteriovenous Malformations. Issue 1 (13th March 2019) - Liew, Jason A; Yang, Wuyang; Mashouf, Leila A; Li, Sean; Caplan, Justin M; Tamargo, Rafael J; Huang, Judy
Abstract: BACKGROUND: Spontaneous obliteration (SpO) of untreated arteriovenous malformations (AVMs) is rare with fewer than 100 cases reported. The incidence and predisposing factors of SpO remain unclear, impeding our understanding of lesion progression in untreated patients. OBJECTIVE: To determine the incidence rate and predisposing factors of SpO in a North American cohort. METHODS: AVMs were retrospectively evaluated at our institution for over 25 yr. Untreated AVMs were divided into 2 groups: SpO-AVMs and non-SpO-AVMs. All statistical results were based on univariate analyses. Incidence was generated from counts of SpO over the untreated interval in patient years from birth until obliteration, treatment, or last follow-up. RESULTS: One hundred fifty-four patients had untreated AVMs; SpO was observed in 4. Average ages were 49.0 ± 23.6 and 48.7 ± 20.4 yr in the SpO-AVM and non-SpO-AVM group, respectively ( P  = .98). Average AVM sizes were 2.0 ± 1.8 cm (SpO-AVMs) and 3.7 ± 2.6 cm (non-SpO-AVMs, P  = .25). All SpO-AVMs and 40 (27.0%) non-SpO-AVMs had a ruptured presentation ( P  = .006). A single draining vein was observed in all SpO-AVMs and 39 (32.8%) non-SpO-AVMs ( P  = .01). Deep venous drainage was not observed in any SpO-AVMs, but in 81 (57.9%) non-SpO-AVMs ( P =  .04). Mean follow-up time was 37.0 ± 42.6 and 75.6 ± 161.7 mo in SpO-AVM and non-SpO-AVMs patients, respectively. Of the 2 SpO-AVM patients with postobliteration follow-up, 1 experienced recanalization. From a 672-patient cohort, the incidence of SpO over 28 961 patient years was 0.014%. CONCLUSION: SpO-AVMs have an annual incidence rate of approximately 0.014% and tend to present with rupture, a single draining vein, and superficial venous drainage. Expectation of SpO for untreated AVMs is not justified, and patients should anticipate life-long hemorrhagic risk for untreated AVMs.